In-home environment and happiness among older adults in Thailand - Pekalee, Alongkorn; Gray, Rossarin Soottipong (Frontiers in Public Health, 2023)
Background The fact that housing can play a critical role in maintaining the health and independence related to happiness of the older population has been studied in more developed countries. However, research on the effect of housing conditions on happiness is rare in less developed countries. This study aimed to construct and test a structural equation model describing the structural relationship among personal aspects (living alone and physical disability), in-home environment (sleeping place and toilet/bathroom), and happiness among older adults in Thailand. Method The data on the population age 75 years or over were extracted from the 2017 national Survey of Older Persons in Thailand (n = 7,829). Results The median age of the sample population was 79. Almost 60 percent were women. The structural equation model showed a good fit with the data. Living alone did not directly influence happiness. Physical disability had a statistically significant negative direct effect on happiness. In-home environment not only had an impact on happiness directly, but also moderated the relationship between physical disability and happiness. Conclusion The research suggested that interventions to improve happiness of older adults, particularly those with physical disability, should aim to adapt their housing, including sleeping place and toilet design.